2013
DOI: 10.1208/s12248-013-9535-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Metabolic Enzymes and the Pharmacokinetics of Indapamide in Taiwanese Subjects

Abstract: Abstract. To understand the genetic makeup and impact on pharmacokinetics (PK) in the Taiwanese population, we analyzed the pharmacogenetic (PG) profile and demonstrated its effects on enzyme metabolism using indapamide as an example. A multiplex mass spectrometry method was used to examine the single nucleotide polymorphism (SNP) profile of eight major phases I and II metabolic enzymes in 1,038 Taiwanese subjects. A PG/PK study was conducted in 24 healthy subjects to investigate the possible effects of 28 SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This finding also does not seem to be in concordance with the available literature on the distribution of these two variants in other ethnic groups. However, like the CYP2C19*17 , the distribution of particularly the CYP2C19* 2 is also known to vary among ethnic populations [41,49–58]. For example, a study by the European Atherosclerosis Research Study showed a higher prevalence of increased on‐treatment platelet reactivity to clopidogrel corresponding to a higher CYP2C19*2 allele carrier status in African‐American patients undergoing PCI compared with their white counterparts, leading to the conclusion that the AA genotype predisposed individuals to a higher risk of ischaemic complications in the former group [59].…”
Section: Discussionmentioning
confidence: 99%
“…This finding also does not seem to be in concordance with the available literature on the distribution of these two variants in other ethnic groups. However, like the CYP2C19*17 , the distribution of particularly the CYP2C19* 2 is also known to vary among ethnic populations [41,49–58]. For example, a study by the European Atherosclerosis Research Study showed a higher prevalence of increased on‐treatment platelet reactivity to clopidogrel corresponding to a higher CYP2C19*2 allele carrier status in African‐American patients undergoing PCI compared with their white counterparts, leading to the conclusion that the AA genotype predisposed individuals to a higher risk of ischaemic complications in the former group [59].…”
Section: Discussionmentioning
confidence: 99%
“…For torsemide, it was shown that CYP2C9*3 resulted in lower oral clearance and metabolite formation clearance [ 33 ]. In the study of Wang et al, patients with homozygous variants of CYP2C9 rs4918758, which showed lowered CYP2C9 activity, had higher C max and AUC and lower clearance of indapamide [ 34 ]. As CYP2C9 is involved in the metabolism of several antihypertensive agents, CYP2C9 loss-of-function alleles may increase the parent drug level.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies demonstrating that genetic differences are associated with different metabolic activity of chemicals, including drugs [44][45][46]. As noted above, erlotinib is metabolized by CYP3A4, CYP1A2 and CYP1A1.…”
Section: Discussionmentioning
confidence: 99%